2007
DOI: 10.1038/laban1007-51
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immune and adverse effects induced by AdjuVac and Freund's complete adjuvant in New Zealand white rabbits (Oryctolagus cuniculus)

Abstract: Though Freund's complete adjuvant effectively increases immune response to vaccines in various species, its potentially severe inflammatory effects have led many animal researchers to seek alternative immunological adjuvants. In a study of New Zealand white rabbits, the authors compared the immune and adverse effects of Freund's complete adjuvant with the effects of two formulations of AdjuVac, an immunological adjuvant previously developed by their group. All three adjuvants improved humoral immune response b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…However, the use of GnRH vaccines as contraceptive agents in wildlife management has been limited by effective duration, multiple treatments to stimulate adequate antibody response, and deleterious side effects associated with the use of the controversial Freund complete adjuvant (FCA) [4,5]. Recently, an alternative adjuvant (AdjuVac) containing mineral oil and mycobacteria derived from a Johne disease vaccine (Mycopar; Fort Dodge Animal Health, Fort Dodge, IA) has been developed and may be as effective as FCA but is associated with fewer lesions [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of GnRH vaccines as contraceptive agents in wildlife management has been limited by effective duration, multiple treatments to stimulate adequate antibody response, and deleterious side effects associated with the use of the controversial Freund complete adjuvant (FCA) [4,5]. Recently, an alternative adjuvant (AdjuVac) containing mineral oil and mycobacteria derived from a Johne disease vaccine (Mycopar; Fort Dodge Animal Health, Fort Dodge, IA) has been developed and may be as effective as FCA but is associated with fewer lesions [11].…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism for inducing infertility is not yet certain (Molenaar et al ), but the presence of high anti‐GnRH antibody titers is correlated with infertility in a variety of species (Fagerstone et al ). Numerous GnRH vaccines have been developed and successfully used for decades in physiological research to interrupt the hormonal pathway that controls ovulation (Powers et al ), but their use was not feasible for free‐ranging wildlife because their short duration of action created the need for multiple treatments, and because they contained the controversial Freund's complete adjuvant, which can cause severe injection site reactions (Fagerstone et al , Gray and Cameron ).…”
mentioning
confidence: 99%
“…It has long been suggested that the granuloma formed at the injection site when using mineral oil is related to the fact the mineral oil cannot be metabolized by the animal. Powers et al (2007) attempted to answer this question by comparing vaccines made of mineral oil as compared to vegetable oil (squalene). They found that there was little difference in the injection site reaction between the two forms of oil.…”
Section: Mineral Oil Vs Vegetable Oil (Squalene)mentioning
confidence: 99%
“…It is known that killed bacteria in the adjuvant have increased the injection site reaction (Powers et al 2007). We have decreased the amount of killed bacteria in the AdjuVac ™ adjuvant to reduce its negative effect.…”
Section: Avium-free Water-soluble Adjuvantsmentioning
confidence: 99%